Structural, elastic and optical properties of (80-x)B2O3-xTeO2-10Li2O-10Al2O3 mixed network former glass system / Nurul Ain Mohd Samsudin - Mohd Samsudin, Nurul Ain (2021)
Mixed glass former of composition (80−x)B2O3-xTeO2-10Li2O-10Al2O3 (x = 10 mol% to 60 mol%) glasses were prepared by melt-quenching technique to investigate the effects of mixing B2O3 and TeO2 glass formers on structural, elastic and optical properties of the glass system. Structural analysis using FTIR spectroscopy revealed competition between TeO2 and B2O3 formers where TeO4 functional group indicates bridging oxygen, BO decreased with increasing TeO2 content, while BO4 units indicates bridging oxygen, BO fluctuated below 40 mol% before finally increasing suggesting BO4 units become dominant above 40 mol% TeO2. At x = 40 mol% TeO2 content, the observed minima in independent elastic moduli (longitudinal, CL (45.6 GPa) and shear, μ (15.2 GPa)) together with Bulk, K (25.4 GPa) and Young’s, Y (38.0 GPa) modulus were due to presence of high concentration of TeO3 and BO3 units which indicates that non-bridging oxygen, NBO deteriorates the rigidity of the glass. This suggest that competition between TeO2 and B2O3 glass formers at 40 mol% is most intense and destructive to the glass structure.